2017
DOI: 10.1128/iai.00824-16
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon-Regulated Chemokines in Leishmania donovani Infection in the Liver

Abstract: In the livers of C57BL/6 mice, gamma interferon (IFN-␥) controls intracellular Leishmania donovani infection and the efficacy of antimony (Sb) chemotherapy. Since both responses usually correlate with granulomatous inflammation, we tested six prominently expressed, IFN-␥-regulated chemokines-CXCL9, CXCL10, CXCL13, CXCL16, CCL2, and CCL5-for their roles in (i) mononuclear cell recruitment and granuloma assembly and maturation, (ii) initial control of infection and self-cure, and (iii) responsiveness to Sb treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
1
10
0
1
Order By: Relevance
“…LFA-1 expressed by liver Trm cells and its interaction with ICAM-1 expressed on hepatocytes and/or LSECs has also been shown to be critical for retention of these T cells in the liver (McNamara et al, 2017). Because the expression of receptor-ligand pairs such as these can be affected by cytokines induced by CpG or poly(I:C) (Murray et al, 2016;Sacher et al, 2002;Tohyama et al, 2007;Wuttge et al, 2004), it is feasible that initial retention of precursors within the liver sinusoids is mediated by adjuvants, leading to greater Trm cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…LFA-1 expressed by liver Trm cells and its interaction with ICAM-1 expressed on hepatocytes and/or LSECs has also been shown to be critical for retention of these T cells in the liver (McNamara et al, 2017). Because the expression of receptor-ligand pairs such as these can be affected by cytokines induced by CpG or poly(I:C) (Murray et al, 2016;Sacher et al, 2002;Tohyama et al, 2007;Wuttge et al, 2004), it is feasible that initial retention of precursors within the liver sinusoids is mediated by adjuvants, leading to greater Trm cell formation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Murray et al (2016) , in experiment performed in the L. donovani -infected livers of gene-deficient C57BL/6 mice (CXCL10-/- and CXCR3-/) showed that CXCL10 may promote anticipated granuloma assembly, however, may hinder early parasite control and may has no role in conversion of developing granulomas to histologically mature-appearing structures. Therefore, CXCL10 appears to paradoxically promote liver infection too.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that CD4 T cells promote MDM recruitment to the lung, thereby providing new bacterial targets, may help explain the increased proportion of infected MDM in immunized animals. This recruitment likely relates to T cell production of cytokines, such as IFN-g and TNF, which are known to trigger the release of chemokines that act on MDM (e.g., CCL2 and CXCL10) (16).…”
Section: The Journal Of Immunologymentioning
confidence: 99%